Sudden cardiac death: Epidemiological profile in the metropolitan area of Goiania - da Silva Menezes Junior, Antonio; Neves de Souza Faria, Alexandre; Alves Ribeiro de Faria, Ricardo (JOURNAL OF CARDIAC ARRHYTHMIAS, 2018)
Background: Sudden cardiac death is an important event which has an impact on public health and is the most lethal manifestation of heart disease. This study is aimed at describing the characteristics of sudden cardiac death in the metropolitan area of Goiania (GO). Methods: This study examined 2,681 necropsy reports of which 314 were selected as sudden cardiac death. Data such as gender, age, location and time of death, presence of smoking, comorbidities such as hypertension, diabetes mellitus, dyslipidemia and Chagas disease history were collected. Results: Among 314 cases of sudden cardiac death, the most affected patients were males, between 60 and 70 years of age. The most common location for the event was the patient’s own house, and most of them occurred in the morning. Hypertension was the most prevalent comorbidity, with a high incidence (58.9%). More than 10% of the patients had a history of Chagas disease. Conclusion: A better understanding of sudden cardiac death in the metropolitan area should be further studied. Understanding the local epidemiological profile is a crucial step towards the development of preventive strategies that must be implemented by political leaders.